Gambaran Tingkat Depresi Pada Lansia di Wilayah Kerja Puskesmas Sidomulyo Rawat Jalan - Fikri Erwanto; Herlina; Aminatul Fitri (Jurnal Vokasi Keperawatan (JVK), 2023)
Depression is a psychological disease that is rarely detected but can directly reduce the quality of life of sufferers, especially the elderly. The purpose of this study was to describe the level of depression in the elderly in the working area of ​​the outpatient sidomulyo health center. Descriptive analytic research design with a purposive sampling approach, the study was located in the working area of ​​the sidomulyo outpatient health center in pekanbaru city with 100 elderly respondents aged over 60 years. The measuring instrument is the geriatic depression scale (gds) questionnaire which has been tested for validity and reliability. The description of the level of depression in the elderly in the working area of ​​the sidomulyo health center can be concluded that the highest level of depression is mild depression (40%), while the characteristic results show that the most age is 60-69 years (56%), the sex of the majority is female (60 %), the majority last education was high school (30%), married status, most of them don't have a partner/not married (55%), and the majority of respondents don't work anymore (61%), and most of the elderly have physical health problems (74%). It was found that the highest levels of depression were mild depression (40%), moderate depression (38%), severe depression (4%), and those who did not experience depression (18%), so that the level of depression in the elderly in the work area outpatient sidomulyo health center with the most mild depression category. Future researchers, it is hoped that they can develop research with more samples and look for risk factors associated with depression in the elderly.